Exponential Time-Dependent Demand (EOQ) Model for Decaying Goods with Shortages - Chakraborty, Ayan (International Journal of Computer Sciences and Engineering, 2026)
In this model, over a predetermined planning period, we study the inventory replenishment strategy for a depreciating good with an exponential time demand function. To reduce the average system cost, the amount of reorders, the gap between reorders, and the gaps between shortages within a given time frame are all estimated. How the approach works is demonstrated by one numerical example. Considering its sensitivity, the significance of the various variables in this model is assesse